2012
DOI: 10.1002/pds.2340
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of validated methods for identifying ventricular arrhythmias using administrative and claims data

Abstract: Background Drug-induced pro-arrhythmia is a serious and unexpected event. Large administrative and claims databases can potentially identify drugs or interactions leading to cardiac arrhythmias. The purpose of this study is to evaluate the evidence supporting the validity of algorithms or codes to identify ventricular arrhythmias using administrative and claims data. Methods A search of MEDLINE database is supplemented by manual searches of bibliographies of key relevant articles. We selected all studies in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 18 publications
3
47
0
Order By: Relevance
“…In previous studies assessing the accuracy of ICD-9 and ICD-10 codes for cardiac arrhythmia (ventricular and supraventricular), the positive predictive value (truly have the condition when code is present) exceeded 80%. [34][35][36][37] We performed a manual review of 202 charts in our region and confirmed a positive predictive value of 92% (95% confidence interval [CI] 87%-95%) for the set of codes used in this study to detect ventricular arrhythmia. Vital statistics for allcause mortality are coded accurately in our data sources, with a sensitivity of 97.8% and specificity of 100% for the finding of death.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies assessing the accuracy of ICD-9 and ICD-10 codes for cardiac arrhythmia (ventricular and supraventricular), the positive predictive value (truly have the condition when code is present) exceeded 80%. [34][35][36][37] We performed a manual review of 202 charts in our region and confirmed a positive predictive value of 92% (95% confidence interval [CI] 87%-95%) for the set of codes used in this study to detect ventricular arrhythmia. Vital statistics for allcause mortality are coded accurately in our data sources, with a sensitivity of 97.8% and specificity of 100% for the finding of death.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies also reported a wide range of positive predictive values of cardiac arrhythmia or cardiac arrest in different databases. [33][34][35] …”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Potential incident events and all deaths were investigated in detail based on initial identification through International Classification of Diseases diagnostic codes and the database of the CCHIA, which was validated previously. [7][8][9][10] Part II: Clinical characteristics and occurrence of VT/VF in the single-center cohort This retrospective, longitudinal study included patients with symptomatic AF (European Heart Rhythm Association [EHRA] score II-IV) from the Taipei Veterans General Hospital from September 2002 to November 2013. Exclusion criteria were age o18 years or 480 years, previous implantation of pacemaker or defibrillator, presence of left atrial thrombus, active infection or sepsis, pregnancy, unstable angina, prior myocardial infarction, valvular heart disease, prior history of VT/VF, life expectation o12 months, mental disease, inability to follow-up, or coexisting diseases for which antiarrhythmic treatment was contraindicated.…”
Section: Part I: Propafenone and Risk Of Vt/vf In The Nationwide Cohortmentioning
confidence: 99%